MR Imaging and Histologic Features of Capillary Telangiectasia of the Basal Ganglia - Castillo, Mauricio (AJNR Am J Neuroradiol, 2001)
Summary: Capillary telangiectasias are being recognized with increasing frequency on MR imaging studies. Most are located in the brain stem and show slightly increased signal intensity on T2-weighted images, low signal intensity on T2*-weighted images (reflecting the presence of deoxyhemoglobin), and contrast enhancement. These findings are considered fairly typical for capillary telangiectasia, and pathologic correlation is not generally pursued. We present a case of a proven capillary telangiectasia in the basal ganglia. The imaging features of the lesion were identical to those described for capillary telangiectasias in the brain stem.